THE MEANING OF VIRTUAL SPACE IN THE ARCHITECTURE OF MUMBAI: A PHENOMENOLOGICAL STUDY OF VIRTUAL REALITY USERS IN INTERIOR DESIGN - N.Z., Singh,; S.R., Rajhev, (JoDA Journal of Digital Architecture, 2025)
The development of virtual reality (VR) technology has transformed the way designers and users perceive and interact with space within the context of architecture and interior design. However, a deep understanding of the meaning of virtual space from the user's perspective remains limited, particularly in urban contexts such as Mumbai, where physical space is increasingly constrained. This study aims to explore and analyze the meaning of virtual spatial experiences in VR-based interior design in the city of Mumbai using a phenomenological approach. A qualitative research method was employed, utilizing phenomenological inquiry through in-depth interviews, participatory observation, and visual documentation involving twenty participants from diverse professional, academic, and end-user backgrounds engaged with VR technology in interior design. Data were analyzed using the Miles and Huberman technique, with validity ensured through credibility, transferability, dependability, and confirmability tests. The findings reveal that virtual space is not merely perceived as a technical visualization tool, but has evolved into an affective and conceptual realm, emotionally, imaginatively, and personally inhabited by its users. The experience of virtual space demonstrates deep user engagement, significantly shaping perception, understanding, and decision-making throughout the interior design process. These insights broaden conceptual understanding in digital architecture and offer practical implications for more participatory and user-centered design approaches, especially within densely populated urban environments such as Mumbai.